Design and clinical outcome of a novel 3D-printed prosthetic joint replacement for the human temporomandibular joint. (July 2018) - Ackland, David; Robinson, Dale; Lee, Peter Vee Sin; Dimitroulis, George
Abstract: Background: Stock prosthetic temporomandibular joint replacements come in limited sizes, and do not always encompass the joint anatomy that presents clinically. The aims of this study were twofold. Firstly, to design a personalized prosthetic total joint replacement for the treatment of a patient's end-stage temporomandibular joint osteoarthritis, to implant the prosthesis into the patient, and assess clinical outcome 12-months post-operatively; and secondly, to evaluate the influence of changes in prosthetic condyle geometry on implant load response during mastication. Methods: A 48-year-old female patient with Grade-5 osteoarthritis to the left temporomandibular joint was recruited, and a prosthesis developed to match the native temporomandibular joint anatomy. The prosthesis was 3D printed, sterilized and implanted into the patient, and pain and function measured 12-months post-operatively. The prosthesis load response during a chewing-bite and maximum-force bite was evaluated using a personalized multi-body musculoskeletal model. Simulations were performed after perturbing condyle thickness, neck length and head sphericity. Findings: Increases in prosthetic condyle neck length malaligned the mandible and perturbed temporomandibular joint force. Changes in condylar component thickness greatly influenced fixation screw stress response, while a more eccentric condylar head increased prosthetic joint-contact loading. Post-operatively, the prosthetic temporomandibular joint surgery reduced patient pain from 7/10 to 1/10 on a visual analog scale, and increased intercisal opening distance from 22 mm to 38 mm. Interpretation: This study demonstrates effectiveness of a personalized prosthesis that may ultimately be adapted to treat a wide-range of end-stage temporomandibular joint conditions, and highlights sensitivity of prosthesis load response to changes in condylar geometry. Highlights: We developed a personalized 3D-printed prosthesis for the temporomandibular joint. Condylar component thickness greatly influenced fixation screw stress response. Condylar head eccentricity increased prosthetic joint-contact loading. The prosthesis reduced pain and increased intercisal opening distance post-operatively.